PENGARUH RASIO RECYCLE TERHADAP PRODUKSI BIOGAS MENGGUNAKAN REAKTOR TANGKI BERPENGADUK BERBANTUKAN MEMBRAN ULTRAFILTRASI PADA KONDISI TRANSISI (45 oC) - Bambang Trisakti; Irvan; M.Taufan Anantama; Arbie Saldi Zusri; Alfian Haikel Lubis; Sri Eka Cahyani (Jurnal Teknik Kimia USU, 2019)
Anaerobic digestion is one of solution to environmental problems and energy sources for current energy needs. In anaerobic digestion, organic material is degraded by bacteria, which is carried out without oxygen, and converts it to a mixture of methane and carbon dioxide. POME can be degraded anaerobically in anaerobic digester to produce biogas. This study aims to increase the conversion of biogas produced using a 2 liter Continuous Stirred Tank Reactor (CSTR) type digester in the methanogenesis process by recycling the effluent produced through the ultrafiltration membrane in a transition condition (45oC). The process is carried out by varying the recycle ratio, which is 0%, 15% and 25% on HRT 6 days with a condition of pH 7 ± 0.2. The highest average biogas production was achieved at the 25% recycle ratio of 33.15 x 10-5 L / mg VS. day, with the composition of methane, carbon dioxide and hydrogen sulfide each of 79%; 19%; and 0.006%, with degradation of VS and COD of 39.58% and 66.33% respectively. For the composition of the highest CH4 content obtained at a variation of the 15% recycle ratio which is equal to 85% while for the composition of carbon dioxide, and hydrogen sulfide each is 14%; and 0.0076%.